Friends in strange garments - Upjohn, Anna Milo, 1868-1951; Dunn, Arthur William, 1868-1927 (Salt Lake City, UT : Project Gutenberg, 2024)
"Friends in Strange Garments" by Anna Milo Upjohn is a collection of illustrated stories written in the early 20th century. The work focuses on the lives of children from various cultures, showcasing both their differences in customs and clothing while emphasizing the universal traits of kindness and friendship among them. Each story highlights the everyday experiences of children in countries like Palestine, Turkey, Greece, and beyond. The opening of the book begins with an introduction that sets the tone for the stories to follow, describing the author's observations of children during her time as a relief worker in Europe after World War I. It emphasizes the need to find similarities and friendship amidst cultural differences. The first story, "In the Wilderness," introduces Rahmeh, a young girl living in the Jordan Valley, as she prepares for a journey to Jerusalem with her brother Yussef. The narrative beautifully depicts their daily life, the bond with their pet animals, and the excitement of adventure, all while laying the groundwork for a deeper exploration of friendship and understanding in diverse environments. (This is an automatically generated summary.)
Introduction, by Arthur W. Dunn -- In the wilderness (Palestine) -- The Pigeon Mosque (Turkey) -- The road to Arcadia (Greece) -- The Christmas lanterns (Greece) -- Draga's entrance examinations (Macedonia) -- The truce (Albania) -- The Skanderbeg jacket (Albania) -- Mirko and Marko (Montenegro) -- Todor's best clothes (Bulgaria) -- Kossovo Day (North Serbia) -- The fairy ring (Roumania) -- Great Amber Road (Czecho-Slovakia) -- The lost brook (Czecho-Slovaka) -- Michael makes up his mind (Poland) -- Elena's ciambella (Italy) -- An everyday story (France).
Illustrated by the author.
Release date is 2024-09-16
Susan E., David E. Brown, and the Online Distributed Proofreading Team at https://www.pgdp.net (This file was produced from images generously made available by The Internet Archive)
Keywords: Children -- Balkan Peninsula -- Juvenile fiction; Children -- Europe -- Juvenile fiction; Children -- Palestine -- Juvenile fiction; Children -- Turkey -- Juvenile fiction